Mbolo Rasa Sebagai Produktivitas Budaya Dalam Merawat Moderasi Antar Umat Beragama - Junaidin, Junaidin (LP2M Universitas Islam Ahmad Dahlan, 2024)
This research aims to review, describe, and analyze the Mbolo Rasa culture within the framework of interfaith moderation in Bima. The research method used is a mixed-method approach, with an Explanatory Sequential Design. Data collected was then analyzed using Miles and Huberman's theory through the following steps: 1) data reduction, 2) data display, and 3) conclusion drawing/verification. The findings indicate that Mbolo Rasa has a significant impact on building social harmony and interfaith cohesion. By applying the values of mutual cooperation and involving community leaders, this tradition becomes an effective tool for strengthening solidarity and addressing social conflicts. From a theoretical perspective, Mbolo Rasa meets the criteria for social capital by reinforcing social bonds, leveraging intergroup contact to foster tolerance, and developing collective action to solve common issues. These results show that local traditions can play an important role in promoting peace and social stability, especially in religiously diverse communities.